2014
DOI: 10.1108/ijes-02-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Managing boundaries at the accident scene – a qualitative study of collaboration exercises

Abstract: Purpose – The purpose of this paper is to identify what is practiced during collaboration exercises and possible facilitators for inter-organisational collaboration. Design/methodology/approach – Interviews with 23 participants from four collaboration exercises in Sweden were carried out during autumn 2011. Interview data were subjected to qualitative content analysis. Findings – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…Local, professionally trained emergency responders handle most daily emergencies [18]. A crisis however, is more transboundary in nature, and rarely confined by administrative and geographical boundaries [19].…”
Section: Introductionmentioning
confidence: 99%
“…Local, professionally trained emergency responders handle most daily emergencies [18]. A crisis however, is more transboundary in nature, and rarely confined by administrative and geographical boundaries [19].…”
Section: Introductionmentioning
confidence: 99%
“…A review of crisis management literature indicates that the majority of the studies were concerned with the "core" actors, that is, different types of professional preparedness and emergency services (Andersson, Carlstrom, Ahgren, & Berlin, 2014;Berlin & Carlstr€ om, 2009;Jerzy, 2016) and organizations working in high-reliability environments (Hales & Chakravorty, 2016;Mousavi et al, 2018;Roberts & Bea, 2001). Another stream of research examines more "peripheral" emergency actors, particularly different types of organized (Benson, Twigg, & Myers, 2001;Kapucu, Arslan, & Demiroz, 2010;Robinson, Murphy, & Bies, 2014) and unorganized volunteers (Barsky et al, 2007;Harris et al, 2017) and their relationship to the core actors (Egan & Tischler, 2010;Johansson, Danielsson, Eriksson, Kvarnl€ of, & Karlsson, 2018;Kvarnl€ of & Johansson, 2014;Rivera, 2016;Scanlon, Helsloot, & Groenendaal, 2014).…”
Section: Background and Previous Researchmentioning
confidence: 99%
“…Earlier studies have shown that the number of visits to the ED can be reduced if health‐care providers integrate and collaborate by establishing reliable reporting routines, access to information such as medical data, and an open‐minded approach between staff from the organisations involved . Patients with multifaceted needs cause conflicts between health‐care entities in assessment of the patients' needs and determination of responsible unit for delivering health care, resulting in longer transfer time between the units …”
Section: Introductionmentioning
confidence: 99%
“…18 Patients with multifaceted needs cause conflicts between health-care entities in assessment of the patients' needs and determination of responsible unit for delivering health care, 19 resulting in longer transfer time between the units. 20,21 Another important internal factor is the lack of a reliable triage with good continuity, which prevents a smooth inflow of patients within the hospital and between different units. One remedy calls for the use of senior physicians to increase the competence of the triage team, thus improving the sensitivity and specificity of triaging at the ED and decreasing LOS.…”
Section: Introductionmentioning
confidence: 99%